Evaluation of micro-weathering index and weathering grade of diverse geomorphic features of proterozoic terrain applying Schmidt hammer. (4th May 2023) - Karmakar, Manas; Banerjee, Monali; Ghosh, Debasis
ABSTRACT: The Upper Subarnarekha Kangsabati Interfluve (USKI) belongs to the eastern margin of CGGC, which is part of East Indian Shield. This Proterozoic (1.72–1.87 Ga) terrain had have experienced intensive weathering processes over the long period under different climatic conditions. A total number of 965 Rebound ( R ) value were collected from eight geomorphic features located in the USKI. In the present study, an attempt has been made to synthesize the history and variation in intensity of weathering using Schmidt hammer (SH). The degree of weathering is calculated using micro-weathering index, which is formulated on Schmidt hammer R -values, collected from deeply weathered (DW) and relatively less weathered (RLW) rock surfaces. The results of the study revealed the different response of diverse types of rock to the geomorphic processes. The weathering grade of each identified geomorphic features has been computed and the results revealed that seven features belong to moderately weathered (grade III) out of eight identified features. The present study is a unique attempt considering multi-cyclic evolution of CGGC to understand the degree of weathering of these studied features, belonging from USKI. This study helps to understand the weathering grade of studied features in quantitative way.